Mutation screening of the USH2A gene in retinitis pigmentosa and USHER patients in a Han Chinese population. (October 2018) - Huang, Lulin; Mao, Yao; Yang, Jiyun; Li, Yuanfeng; Li, Yang; Yang, Zhenglin
Abstract Objectives USH2A encodes for usherin, a basement membrane protein in the inner ear and retina.USH2A can cause retinitis pigmentosa (RP) with or without hearing loss. The aim of this study was to detectUSH2A mutations in a Chinese cohort of 75 small RP families and 10 Usher syndrome families. Methods We performed a direct Sanger sequencing analysis of theUSH2A gene to identify mutations for this cohort. Results We identified a total of eight mutations in four of the 75 small RP families (5.3%) and two mutations in one of the 10 Usher families (10%); all families were detected to have compound heterozygous mutations. In families with nonsyndromic RP, we identified the compound heterozygous mutations p.Pro4818Leuand p.Leu2395Hisfs*19 in family No. 19114, p.Arg4493His and p.His1677Glnfs*15 in family No.19162, c.8559-2A > G and p.Arg1549* in family No.19123 and p.Ser5060Pro and p.Arg34Leufs*41 in family No.19178. We also identified the heterozygous mutations p.Arg3719His and p.Cys934Trp in family No.19124, which was the Usher syndrome family. These mutations were predicted to be harmful by SIFT, PROVEAN, Mutation Taster or PolyPhen-2. Conclusions Our results revealed six novel mutations in theUSH2A gene in a Chinese population, which is beneficial for the clinical use of genetic testing ofUSH2A in patients with autosomal-recessive or sporadic RP and Usher syndrome.